Catalytic conversion of corncob to furfuryl alcohol in tandem reaction with tin-loaded sulfonated zeolite and NADPH-dependent reductase biocatalyst. Issue 6 (January 2021) - Li, Yuan-Yuan; Li, Qing; Zhang, Peng-Qi; Ma, Cui-Luan; Xu, Jian-He; He, Yu-Cai
Graphical abstract: Highlights: Tin-loaded sulfonated zeolite (Sn-zeolite) catalyzed biomass into furfural (FUR). An NADPH-dependent reductase was used to catalyze FUR into furfuryl alcohol (FFA). Chemical catalysis of corncob and biocatalysis of FUR were optimized. Corncob was effectively catalyzed to FFA. Chemoenzymatic synthesis of FFA from biomass was established in one-pot manner. Abstract: In this study, tin-loaded sulfonated zeolite (Sn-zeolite) catalyst was synthesized for catalysis of raw corncob (75.0 g/L) to 103.0 mM furfural at 52.3% yield in water (pH 1.0) at 170 °C. This corncob-derived furfural was subsequently biotransformed with recombinant E. coli CG-19 cells coexpressing NADPH-dependent reductase and glucose dehydrogenase at 35 °C by supplementary of glucose (1.5 mol glucose/mol furfural), sodium dodecyl sulfate (0.50 mM) and NADP + (1.0 μmol NADP + /mmol furfural) in the aqueous catalytic media (pH 7.5). Both sodium dodecyl sulfate (0.50 mM) and Sn 4+ (1.0 mM) could promote reductase activity by 1.4-folds. Within 3 h, furfural was wholly catalyzed into furfuryl alcohol. By combining chemical catalysis with Sn-zeolite and biocatalysis with CG-19 cells in one-pot, an effective and sustainable process was established for tandemly catalyzing renewable biomass into furfuryl alcohol under environmentally-friendly way.